Evaluation of different inclusion levels of dry live yeast impacts on various rumen parameters and in situ digestibilities of dry matter and neutral detergent fiber in growing and finishing beef cattle. (4th November 2019) - Cagle, Caitlyn M; Batista, Luiz Fernando D; Anderson, Robin C; Fonseca, Mozart A; Cravey, Maztt D; Julien, Christine; Tedeschi, Luis O
Abstract: This study evaluated the effects of supplementing dry live yeast (LY ; Saccharomyces cerevisiae ) on in vitro gas production (IVGP ) fermentation dynamics, pH, and CH4 concentration at 48 h, and in situ rumen parameters and digestibility of DM (DMD ) and NDF (NDFD ) of growing cattle during 3 feeding phases: grower (GRW ) for 17 d (38% steamed-flaked corn; SFC ), transition (TRANS ) for 15 d (55.5% SFC: 1.2 Mcal/kg NEg ), and finisher (FIN ) for 13 d (73% SFC: 1.23 Mcal/kg NEg ). Twenty British-crossbred, ruminally cannulated steers (183 kg ± 44 kg) 6 mo of age were blocked by weight into 5 pens containing Calan gate feeders and received a control (CON ) diet (17.2% CP, 35.8% NDF, 86.7% DM) without LY on days −12 to 0. After that, animals were randomly assigned to treatments (TRT ), 5 animals per TRT: CON or LY at inclusion rates of 5 g/d (LY1 ), 10 g/d (LY2 ), or 15 g/d (LY3 ) top dressed every morning at 0800 for 45 d. The DMD and NDFD were assessed during 7 separate collection days using in situ nylon bags containing 5 g of GRW, TRANS, or FIN diets, incubated at 1200 for 48 h. Protozoa counts (PC ) were determined during 5 collection periods. Data were analyzed as a repeated measure within a randomized complete block design, assuming a random effect of the pen. For GRW, TRT altered the total gas production of the nonfiber carbohydrate (NFC ; P = 0.045) and the fractional rate of degradation (kd ) of the fiber carbohydrate (FC ) pool ( P = 0.001) in a cubic pattern ( P ≤ 0.05): LY2 had the most gas production and fastest kd. TRT also influenced DMD ( P = 0.035) and NDFD ( P = 0.012) with LY2 providing the greatest digestibility. For TRANS, TRT tended to affect the NFC kd ( P = 0.078) and influenced pH ( P = 0.04) and DMD (P < 0.001) in which LY2 yielded the fastest kd, highest pH, and greatest DMD. For FIN, there was an effect of TRT on total gas production ( P < 0.001) and kd ( P = 0.004) of the NFC pool, FC kd ( P = 0.012), in vitro CH4 concentration ( P < 0.001), PC ( P < 0.001), DMD ( P = 0.039), and NDFD ( P = 0.008). LY1 had the highest PC and provided the greatest DMD and NDFD. LY2 had the fastest kd of both the NFC and FC pools and had the least CH4 concentration. LY3 had the greatest NFC gas production. No specific dose–response pattern was observed, but 10 g/d provided the most beneficial result for all diets. We concluded that supplementation with LY affected IVGP as well as ruminal parameters and digestibilities.